A comparison of patient reported outcomes between total knee arthroplasty patients receiving the journey II bi-cruciate stabilizing knee system and total hip arthroplasty patients - Snyder, Mark; Sympson, Alexandra; Gregg, Justin; Levit, Alexander (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
Patients who have undergone total hip arthroplasties (THA) tend to report greater satisfaction than those who underwent total knee arthroplasties (TKA). Progress in TKA and THA procedures requires maximizing perceived patient satisfaction, joint-specific and overall function, as well as the return to previously enjoyed physical activities. Dissatisfaction persists in 11–20 % of primary TKA patients while THA dissatisfaction remains low. This study examined if the use of the journey II bi-cruciate stabilizing (JIIBCS) knee implant (Smith & Nephew, Memphis, TN, USA) in TKA patients improved patient satisfaction to equal those reported by equivalent THA patients. Methods: this retrospective analysis matched 48 JIIBCS TKA and 48 THA patients to compare satisfaction at 3 months and 1 year post-operatively. Patient UCLA, and EQ-5D scores were also compared between the JIIBCS TKA and THA. Results: An independent samples t- test or Mann-Whitney U test, showed no difference in outcomes between 96 JIIBCS TKA and THA procedures. Demographics, gender, ASA score, comorbidity and diagnosis were found to be equivalent between groups. There was no statistical significance between JIIBCS TKA and THA patient satisfaction scores at either 3 months (p = 0.398), or one year post-operatively (p = 0.590). The JIIBCS group experienced higher UCLA scores than the THA group at both 3 months (p = 0.028) and 1 year post-operatively (p < 0.001). At 3 months post-operatively, the JIIBCS TKA patients reported superior EQ-5D scores (p < 0.001), but there was no statistically significant difference between groups in EQ-5D scores at one post-operatively, nor in the time taken to return to work, sports, or activities of daily living. Discussion: This retrospective review demonstrated that TKA patients receiving an optimized knee implant experienced non-inferior outcomes and satisfaction compared with clinically similar THA patients.